SISTEM INFORMASI PEMASARAN PENDIDIKAN - Lestari, Tri; Chotimah, Chusnul; Junaris, Imam (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2024)
Competition in the world of education is inevitable, many educational institutions have been abandoned by customers, resulting in negative dynamics in several educational institutions. Meanwhile, Islamic educational institutions, especially schools, are still covered by second-class educational institutions with favorable levels below public educational institutions. There are still many people who lack or even do not know. Therefore, many changes must be made, especially institutions related to the pattern of management. Institutions as educational service providers need to learn and have the enthusiasm to increase customer satisfaction because education is a process that is face to face and continuous. The agency's initiative starts with finding out. In a world full of innovation, competition and expansion, the term marketing needs to be redefined. Marketing of educational services in institutions does not necessarily mean commercialization, but prioritizes the quality of education, and provides excellent service to its stakeholders, thereby providing satisfaction to the community which can be beneficial in increasing the "selling value" of the institution.